Reflektor Jalan Baja Ringan: Intervensi Keselamatan Lalu Lintas di Desa Pasanggrahan - Latukau, Fikry; Sulistiyanto, Ridwan; Syah, Hermawan; Azizah, Anisa Nurul (Universitas Pahlawan Tuanku Tambusai, 2026)
The lack of lighting and the high potential for accidents at night on Argo Raya Street, Pasanggrahan Village, became the basis for implementing a simple road reflector installation program. This activity aims to provide effective visual guidance for road users at accident-prone points. The approach used includes field observation, reflector design using lightweight steel materials, installation at strategic locations, and post-installation visibility evaluation. The results indicate that the presence of reflectors significantly increases the driver's visibility range, clarifies the lane direction, and provides a longer reaction time in low-light conditions. The use of lightweight steel material has proven to be stable, resistant to weather changes, and easy to install, making it a practical solution for rural areas. This program received a positive response from local residents and contributed to increasing awareness regarding driving safety. Overall, this intervention is considered effective and feasible to be replicated in areas with similar characteristics.